Comparative investigation of cell cycle and immunomodulatory genes in mucosal and cutaneous melanomas: preliminary data suggest a potential promising clinical role for p16 and the PD-1/PD-L1 axis - Wrede, Niklas; Hoffmann, Inga; Vollbrecht, Claudia; Koch, Ines; Wolkenstein, Peggy; Klauschen, Frederick; Capper, David; Laffert, Maximilian von; Jurmeister, Philipp (Pathology, research and practice, 2022)
Mucosal melanomas arise from the mucosal lining of various organs. Their etiology is currently unknown and there are no tissue-based methods to differentiate it from cutaneous melanomas. Furthermore, prognostic and predictive markers (e.g. for immune checkpoint inhibition) are lacking. In this study, we aimed to assess the protein expression levels of cell cycle-associated proteins and immune checkpoint markers in a cohort of mucosal melanomas in comparison to cutaneous melanomas and evaluated the effect of potential regulatory mechanisms. We performed immunohistochemistry, DNA methylation analysis and copy number profiling of 47 mucosal and 28 cutaneous melanoma samples. Protein expression of CD117, Ki67 and p16 was higher in mucosal melanomas, while BCL2, Cyclin D1, PD-1 and PD-L1 were overexpressed in cutaneous melanomas. CDKN2A deletions were the most prevalent numeric chromosomal alterations in both mucosal and cutaneous melanoma and were associated with decreased p16 expression. KIT was frequently amplified in mucosal melanomas, but not associated with CD117 expression. On the other hand, amplification of CCND1 lead to Cyclin D1 overexpression. In mucosal melanoma patients high PD-1 expression and high PD-L1 promoter methylation levels were associated with improved survival. PD-L1 expression correlated with response to immune checkpoint inhibitor therapy in the combined group of melanoma patients. Mucosal and cutaneous melanomas show different expression levels of cell cycle-associated and immunomodulatory proteins that are partially regulated by DNA methylation and copy number alterations. PD-1 expression and PD-L1 promoter methylation levels might be a prognostic marker for mucosal melanomas.